Operation and Economic Analysis for Ring Road: Baqubah City as Case Study - Raquim Nihad Zehawi; Ali Hussein Hameed; Yassir Nashaat A Kareem (Journal of Engineering)
Many cities in Diyala governorate are suffering from traffic congestion due to high percentage of through traffic. One of the most applicable solutions to such problem is the construction of ring road by which the through traffic is avoided. In this research, Baqubah city is subjected to economic analyses in order to determine whether the establishment of a peripheral ring road to downgrade the traffic congestion in the city center would be economically feasible. The planned road is divided into three segments linking the three major entries to the city. The first segment is already existing, while the second and third segments are following a predetermined orbital route that has not been utilized yet. Hence, the first segment is not considered in the economic analyses, which included the second and third. The traffic data was collected for all entries, and then the fractions of traffic that expected to utilize the new ring road were estimated and projected for the design lifetime of the road taken as 20 years after two years of design and construction. The suggested road was proved profitable by the use of two economic parameters: the first is the benefit cost ratio, which returned the values of 7.44 and 5.92, for the second and third segments, respectively. The net present value calculations revealed the values of $50,399,966 and $43,991,883 for the second and third segments, respectively.